IMPLEMENTATION OF MASSIVE MIMO IN SUB-6 GHZ AND MMWAVE TECHNOLOGY USING HYBRID PRECODING (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The massive multiple input multiple output (MIMO) uses arrays with many antennas at the BS to provide vast signal amplification by beamforming and high spatial resolution to multiplex many simultaneous users. Although small-scale MIMO technology has been around for decades, the practical gains have been modest due to the small number of antennas which seldom give sufficient spatial resolution to support many spatially multiplexed streams. Massive MIMO has been demonstrated to achieve an order-of-magnitude higher spectral efficiency in real life, with practical acquisition of channel state information (CSI). 3GPP is steadily increasing the maximum number of antennas in long term evaluation (LTE) and since 64 antennas are supported in Release 15, Massive MIMO has become an integral component of 5G. This work implemented these differences and their implications, while dispelling common misunderstandings. Building on this foundation, we suggest appropriate signal precoding schemes and use cases to efficiently exploit Massive MIMO in both frequencies.